PORNOGRAPHY ADDICTION AND ITS PSYCHOSOCIAL IMPACTS IN ADOLESCENTS - Muhammad Nurfathirsyah; Prananjaya, Bintang Arroyantri; Mariana, Mariana (Journal of Psychiatry Psychology and Behavioral Research, 2026)
Introduction: The research aimed to reveal the psychosocial impacts on adolescents who experienced pornography addiction. Methods: A qualitative approach was used; participants were aged 14-25 years. The data was taken from PubMed, Google Scholar, and Portal Garuda. The result showed 7 of the 70 research articles that met the inclusion criteria. Results: The psychosocial impact of addictive consumption of pornography was found in the form of depression, aggressiveness, and antagonistic communication, decreased empathetic tendencies, poor inhibitory control, lower working memory, and anxiety disorder. Discuss: healthcare professional health promotion needs to be performed, and the most important is education about pornography usage and its negative impact on psychosocial health, especially in adolescents. Conclusion: This study shows many negative impacts of pornography addiction from a social aspect, as well as from a neuromechanical aspect. In conclusion, pornography addiction has many negative impacts on psychosocial aspects, such as depression, aggressiveness and antagonistic communication, decreased empathetic tendencies, poor inhibitory control, lower working memory, and anxiety disorders. Pornography addiction, especially in adolescents, has direct and negative adverse effects. Keywords: pornography, addiction, psychosocial, adolescent.